A Case Report of Acute Disseminated Encephalomyelitis (ADEM) that Presents with Signs of Meningitis - Öznur AK (Flora Infeksiyon Hastalıkları ve Klinik Mikrobiyoloji Dergisi, 2004)
Acute disseminated encephalomyelitis (ADEM) being a demyelinating disorder of the central nervous system, may be considered in the differential diagnosis of acute meningitis because of presentation symptoms of fever, headache, and meningismus. We report an ADEM case who presented with meningitis symptoms.